Laboratory Monitoring of Oral Vitamin K Anticoagulation - Moffat, Karen A.; Lewis, Clinton W. (Seminars in Thrombosis and Hemostasis, 2017)
Vitamin K antagonists (VKA) have been used for many years as effective anticoagulant therapy. The laboratory plays a crucial role in measuring the prothrombin time (PT) and calculating the international normalized ratio (INR). Each component of the calculation has the potential to increase error in the final result. This article discusses the laboratory aspects of monitoring VKA including sample requirements, PT, determination of the INR, point of care (POC) testing, external quality assurance/proficiency testing, and reversal strategies for VKA therapy. The implementation of the PT/INR reporting standard was a significant improvement in laboratory medicine. However, further room for improvement exists in the management of PT/INR testing, to clarify the role of POC testing and continue the harmonization process to ensure reliability and reproducibility of INR results.
Keywords: laboratory; monitoring; vitamin K antagonists; prothrombin time; INR